Hidazida 6-hidrazinonicotínica: síntese quimio e regiosseletiva de piridinohidrazonas, ácidos pirazolil-nicotínicos e heterociclos derivados - Paim, Gisele Rocha (2012)
The present research firstly describes the study of methods for the hydrolysis of amide bond [C(O)-N] in 2-(5-trifluoromethyl-5-hydroxy-4,5-dihydro-1H-pyrazol-1-yl)-5-(5-trifluoromethyl-5-hydroxy-4,5-dihydro-1H-pyrazol-1-yl-1-carbonyl)pyridines (2), where alkyl = CH3, aryl = C6H5, 4-OCH3C6H4, 4,4 -BiPh and heteroaryl = fur-2-yl, previously synthesized, aiming at the synthesis of a series of five pyrazolyl-nicotinic acids (3), applying basic conditions (NaOH, EtOH/H2O, 100 oC, 20 h) and their five esters derivatives (4) through reactions of 3 with thionyl chloride and methanol. These compounds were successfully obtained and in pure form with yields of 70 95% for nicotinic acids and between 57 84% for the aforementioned esters. Secondly, the study of the reactivity of 6-hydrazinonicotinic acid hydrazide reagent was developed (1), which presents two different nucleophilic centers in its chemical structure: hydrazine and hydrazide. First, a cyclocondensation reaction of [4+1] type was conducted between 1 and the triethylorthoacetate. This ortho ester, acting as reagent / solvent under reflux for 16 hours, presented no chemical distinction between the two nucleophilic centers in 1, which simultaneously reacted, originating the novel heterocyclic system 3-methyl-6-(5-methyl -1,3,4-oxadiazol-2-yl-[1,2,4] triazolo[4,3-a]pyridine in 82% yield. The chemo-differentiation reactivity of the hydrazine-hydrazide moieties favoring hydrazine function was observed when 1 reacted with aryl and heteroaryl aldehydes in ethanol solvent at 60 °C for 7 hours, resulting in a series of seven new 6-[2-aryl/heteroarylmethylidenehydrazinyl]nicotinohydrazides (7) with 64 - 94% yields. Subsequently, the cyclocondensation reactions of [3 + 2] type involving the hydrazide 7 free function and the 4-alkoxy-4-alkyl(aryl/heteroaryl)-1,1,1-trifluoroalk-3-en-2-ones (8) resulted in a new series of nine 5-[(3-alkyl(aryl/heteroaryl)-5- trifluoromethyl-5-hydroxy-4,5-dihydro-1H-pyrazol-1-yl)carbonylpyridin-2-yl]aryl/ heteroarylaldehyde hydrazones (9) with 45 74% yields. Illustrating the possibility of obtaining other heterocycles, the 6-[2-aryl/heteroarylmethylidenehydrazinyl]nicotinohydrazides, which presents free hydrazide function, and triethylorthoacetate were used as predecessors. Therefore, the oxadiazolyl-pyridine (10) 2-[5-(5-methyl-1,3,4-oxadiazol-2-yl)-pyridin-2-yl]-4-chlorobenzaldehyde hydrazone was obtained in 64% yield when this reaction was developed under reflux for 16 hours. Finally, with the intention of demonstrating the possibility of incorporating the metallocene ferrocene into the organic heterocyclic system under investigation, two 6-[2-ferrocenylmethyl(ethyl)idenehydrazino]nicotinic hydrazide (12) were synthesized with yields from 58 to 72% and a derived series from six 5-[(3-alkyl(aryl/heteroaryl)-5-trifluoromethyl-5-hydroxy-4,5-dihydro-1H-pyrazol-1-yl)carbonylpyridin-2-yl] acetylferrocene/ferrocenecarboxaldehyde hydrazones (13) with yields from 58 to 72%. The compounds were characterized by 1H and 13C {1H} NMR Spectroscopy, Gas Chromatography coupled to Mass Spectrometry (GC-MS), Liquid Chromatography coupled to Mass Spectrometry (LC-ESI-MS/MS) and their purity determined by CHN Elemental Analysis.